Editors' Note: One-Stage, Limited-Resection Epilepsy Surgery for Bottom-of-Sulcus Dysplasia. (13th December 2022) - Lewis, Ariane; Galetta, Steven
Abstract : In "One-Stage, Limited-Resection Epilepsy Surgery for Bottom-of-Sulcus Dysplasia, " Macdonald-Laurs et al. reported that bottom-of-sulcus dysplasia (BOSD) can be safely and effectively resected with MRI and electrocorticography guidance; 33/38 (87%) patients were seizure-free at a median of 6.3 years postoperatively. Hu et al. noted that combined fluorodeoxyglycose-positron emission tomography and MRI can improve sensitivity in detecting these lesions. They also commented that laser interstitial thermal therapy (LITT) may be an effective, less invasive option for BOSD. Harvey and Macdonald-Laurs responded that LITT and stererotactic thermocoagulation (STC) can be considered for certain patients with BOSD, but that these procedures (1) preclude confirmation of epileptogenicity with electrocorticography and the ability to review both histopathology and genetic sequencing; (2) are not feasible in many centers; and (3) can lead to thermal injury in normal areas of the brain. Additional data on the use, durability, and complications of LITT and STC are needed to evaluate the best treatment strategies for BOSD.